Analisis Sosial Budaya terkait Pernikahan Usia Dini di Kepulauan Selayar - Ningsih, Andi Pramesti; Suriah, Suriah; Syafar, Muhammad; Muis, Masyitha; Sukri, Sukri; Abdullah, Muhammad Tahir (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2020)
Background. Marriage at an early age has a negative impact on adolescents in physical, psychological, and biological aspects. Marriage at an early age is closely related to traditions in society such as arranged marriage. Objective. This study aimed to to explore the socio-culture related to early marriage on Selayar Island. Method. This study used a qualitative method with a descriptive phenomenology approach. Informants include youth, parents, health providers, and community heads. Data were collected using in-depth interviews and focus group discussions following the research objectives. Data were analyzed using domain analysis. Results. Three main domains found in this study related to early marriage are: (1) arranged marriage is a factor that supports early marriage (2) social support from the community supporting marriage at an early age because of the prevailing arranged marriage tradition in the society (3) the knowledge possessed by the community and adolescents is still lacking about the impact of early marriage Conclusion: Social culture in the community can be an approach to reducing early marriage.